2014
DOI: 10.1542/peds.2013-1728
|View full text |Cite
|
Sign up to set email alerts
|

Milia en plaque of the Nose: Report of a Case and Successful Treatment With Topical Tretinoin

Abstract: Milia are benign, superficial keratinaceous cysts that present as fine, small white papules. Milia en plaque is a rare, challenging-to-treat variant most often seen in the posterior auricular region. A total of 9 cases of milia en plaque have been reported in the pediatric literature to date. We report a case of milia en plaque of the nose in a 7-yearold boy, a novel site of involvement in the pediatric population, and successful treatment with the use of topical tretinoin. Topical retinoids offer an effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Atopic diathesis was not reported in peer‐reviewed drug‐induced milia case reports or in online forums reporting milia while on isotretinoin. There have been cases showing the successful treatment of milia with topical tretinoin . Additionally, one study suggested that pretreatment with topical tretinoin prevented milia in patients receiving dermabrasion for acne scarring …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atopic diathesis was not reported in peer‐reviewed drug‐induced milia case reports or in online forums reporting milia while on isotretinoin. There have been cases showing the successful treatment of milia with topical tretinoin . Additionally, one study suggested that pretreatment with topical tretinoin prevented milia in patients receiving dermabrasion for acne scarring …”
Section: Discussionmentioning
confidence: 99%
“…There have been cases showing the successful treatment of milia with topical tretinoin. 3 Additionally, one study suggested that pretreatment with topical tretinoin prevented milia in patients receiving dermabrasion for acne scarring. 4 One theory for the pathogenesis of isotretinoin-induced milia is that isotretinoin is converted to all-trans-isotretinoin, activating cellular retinoic acid-binding protein I, which in turn activates the extracellular signal regulated kinase system, causing keratinocyte proliferation and keratinous cyst formation.…”
Section: Discussionmentioning
confidence: 99%
“…It is a variant of primary milia and is most commonly located around the ears or earlobes . Other sites such as the eyelids, medial canthus, submandibular area, nose , mental crease, and supraclavicular area have also been described. The majority of cases are reported in adults between the third and sixth decades of life, with a 3:1 female predominance.…”
Section: Case Reportmentioning
confidence: 99%
“…Patient or family preference typically dictates treatment for cosmetic purposes or, rarely, pruritus. Options include topical tretinoin , minocycline , and destructive methods (e.g., carbon dioxide laser ablation , dermabrasion ), which may be less well tolerated in children. There is only anecdotal evidence of efficacy of any of these treatments for MEP.…”
Section: Case Reportmentioning
confidence: 99%
“…Answers: Manual extraction – Correct. Although there are many treatment options such as topical tretinoin and oral minocycline for MEP,2, 3 manual extraction is the most common treatment.Topical glucocorticoid – Incorrect. So far, there has been no report that MEP is successfully treated with topical glucocorticoid.Photodynamic therapy – Incorrect.…”
mentioning
confidence: 99%